2008
DOI: 10.1002/dvdy.21830
|View full text |Cite
|
Sign up to set email alerts
|

Muscular dystrophy candidate gene FRG1 is critical for muscle development

Abstract: The leading candidate gene responsible for facioscapulohumeral muscular dystrophy (FSHD) is FRG1 (FSHD region gene 1). However, the correlation of altered FRG1 expression levels with disease pathology has remained controversial and the precise function of FRG1 is unknown. Here, we carried out a detailed analysis of the normal expression patterns and effects of FRG1 misexpression during vertebrate embryonic development using Xenopus laevis. We show that frg1 is expressed in and essential for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 21 publications
2
53
1
Order By: Relevance
“…Interestingly frg1 overexpression in this invertebrate model disrupts the body-wall musculature and the muscular organization (Liu et al, 2010). In Xenopus both knock down and overexpression of frg1 resulted in defective growth and morphogenesis of the myotome indicating that precise levels of frg1 must be maintained for normal muscle morphology (Hanel et al, 2009). Together these results strongly suggest an evolutionary conserved function of FRG1 in muscular development.…”
Section: Fshd Region Gene 1 (Frg1)mentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly frg1 overexpression in this invertebrate model disrupts the body-wall musculature and the muscular organization (Liu et al, 2010). In Xenopus both knock down and overexpression of frg1 resulted in defective growth and morphogenesis of the myotome indicating that precise levels of frg1 must be maintained for normal muscle morphology (Hanel et al, 2009). Together these results strongly suggest an evolutionary conserved function of FRG1 in muscular development.…”
Section: Fshd Region Gene 1 (Frg1)mentioning
confidence: 71%
“…Recent studies show the crucial role of FRG1 in maintaining proper muscle structure and function (Hanel et al, 2011;Hanel et al, 2009;Liu et al, 2010). In C. elegans, frg1 protein localized both in nuclei and in the dense bodies that are homologous to vertebrate Z-disk.…”
Section: Fshd Region Gene 1 (Frg1)mentioning
confidence: 99%
“…Scale bars: 50m. orthologs in Xenopus, M. musculus and now C. elegans (Gabellini et al, 2006;Hanel et al, 2009), and the conserved actin-bundling activity of the human FRG1 protein, we propose that FRG1 is likely to localize and function similarly in human muscle (Fig. 4M).…”
Section: Translational Impact Relating To Fshd Pathophysiologymentioning
confidence: 81%
“…However, multiple expression analyses have produced inconclusive, and often contradictory, results with respect to altered mRNA expression levels in FSHD-affected muscle (Arashiro et al, 2009;Gabellini et al, 2006;Jiang et al, 2003;Osborne et al, 2007;Winokur et al, 2003). Circumventing the inconsistencies of the RNA expression data, both mice and Xenopus transgenically overexpressing FRG1 in skeletal muscle exhibit FSHD-like phenotypes (Gabellini et al, 2006;Hanel et al, 2009;). In addition, ubiquitous FRG1 overexpression not only disrupts normal vertebrate muscle development, but also leads to a tortuous vasculature similar to the retinal vasculopathy exhibited by more than 50% of FSHD patients (Gieron et al, 1985;Wuebbles et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a putative role in FSHD, several functional studies of the FRG1 protein have shown it to have a role in both angiogenesis and muscle development by utilising quite different biochemical functions, i.e. alternative RNA splicing and actin bundling (Gabellini et al 2006;van Koningsbruggen et al 2007;Hanel et al 2009;Wuebbles et al 2009;Liu et al 2010;Sun et al 2011). Furthermore, a recent analysis of myoblasts isolated from affected muscle of a transgenic mouse overexpressing FRG1 reported a significant loss of cell proliferation and an increased doubling time not observed in unaffected muscle .…”
Section: Epigenetic Mechanisms Involved In Fshdmentioning
confidence: 87%